Pengaruh Pengawasan dan Sanksi Hukum Terhadap Disiplin Kerja Karyawan pada PT. Bintang Kreasi Aroma - Supriyatno Supriyatno; Maskur Mu’in (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to analyze the influence of monitoring and punishment on work discipline. The population in this study were employees of PT Bintang Kreasi Aroma. The sample in this study amounted to 73 employees. The sampling technique used was non probability sampling with saturated sampling technique. The Methods of data collection using survey method, with the research instrument is a questionnaire and unstructured interview. The data analysis method uses SPSS 25. This study proves that monitoring has a positive effect on work discipline. Punishment has a positive effect on work discipline. Monitoring and punishment together affect work discipline.